Pb-207 NMR chemical shifts of lead tetracarboxylates - Buston, J; Claridge, T; Heyes, S; Bretherton, J; Moloney, M; Stevenson, M (2001)
207Pb NMR spectroscopy was used to investigate 20 lead(IV) tetracarboxylates both in solution and in the solid state by cross-polarization magic angle spinning (CP/MAS) NMR. There is generally good correlation between isotropic chemical shifts in the solid state and those in solution. Multiple CP/MAS NMR isotropic resonances are observed for three of the compounds and are interpreted in terms of multiple molecules in the crystallographic asymmetric unit. From an analysis of the range of, and trends in, the NMR chemical shifts, circumstantial evidence is presented for augmentary coordination by Lewis basic ortho-aromatic substituents of the carboxylate groups. The 207Pb chemical shift anisotropy (CSA) parameters were extracted from analysis of the spinning sideband manifolds of the CP/MAS spectra. The CSA spreads are small in comparison with others reported for 207Pb, and all have positive skew, in contrast to the typical case for lead(II) compounds. Thirteen of the 20 CSA analyses performed show effectively axial CSA tensors. A simple shielding model which rationalizes this typical CSA pattern is presented, based on an analysis of geometric information derived from the two known single-crystal x-ray structures of lead(IV) carboxylates. Copyright © 2001 John Wiley and Sons, Ltd.